PERAN PAJAK KARBON DALAM MENDORONG INVESTASI HIJAU - Prameswari, Ida Ayu Nirma; Ratna, Pande Komang Liana; Dewi , Ni Made Sintya Surya (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
Global warming and rising greenhouse gas emissions require developing countries to accelerate their transition toward a low-carbon economy, despite facing major challenges such as dependence on fossil fuels, limited green financing, and weak regulatory capacity. In this context, carbon tax is viewed as a fiscal instrument capable of providing a strong price signal for industries to reduce emissions while simultaneously directing investment flows toward green sectors. This study aims to analyze the effectiveness of carbon tax in developing countries, its relationship with the increase of green investment, and its role in accelerating the transition to a low-carbon economy. The research employs a qualitative approach through literature review of scientific journals, international reports, and government policies related to carbon pricing and green investment dynamics. The findings indicate that the effectiveness of carbon tax remains low due to minimal tax rates, limited sectoral coverage, and regulatory uncertainty; however, the instrument is proven to enhance green investment when the revenue is allocated productively. Furthermore, carbon tax plays a strategic role in promoting low-carbon economic transformation, particularly when integrated with national energy transition strategies and supported by fiscal incentives that encourage the adoption of clean technologies.